HULL-LESS BARLEY: THE STATE OF STUDY AND PROSPECTS OF USE - E. G. Filippov; E. S. Doroshenko (Зерновое хозяйство России, 2018)
The main places of growing of hull-less barley varieties are considered to be the South-East Asia, mountainous Central and West China with its lowlands. These are the places where there is a great variety of hull-less barley.  The data received with a radio isotope method show that hull-less barley dates back to 7900 years B.C. Thus, hull-less barley appeared significantly later than chaffy barley, which grew in the Pre-Pottery Neolithic (9700-9300 years B.C.). Barley grain is used for making different groats. Barley groats is grain with removed hulls, processed according to a kind of groats. The volume of groats depends on a structure of starch and amount of hulls.  The grain of hull-less barley is free from the hulls and mostly glassy, so the volume of groats received from hull-less barley is much more than from chaffy barley. Barley and pearl barley are made from barley grain. Besides hull-less barley is used as a valuable fodder, especially for monogastric animals. Nowadays the breeding of hull-less barley varieties is being carried out in Canada, Japan, US and Sweden. Comparing chemical structure of hull-less and chaffy barley, we must note that hull-less barley prevails the other one, except in a content of cellulose.  In the foreign scientific works the prior tasks for study are the problems of domestication of hull-less barley, its varieties, tolerance and resistance to pests and diseases. Native literature is devoted to the problems of practical breeding, study of green mass and grain of hull-less barley.